Essays on households\' consumption and saving - Zabot, Udilmar Carlos (2023)
This doctoral dissertation consists of four self-contained essays that address income, consumption, and saving at the household level in Brazil. The common feature among them is the disaggregated data from the Consumer Expenditure Survey (Pesquisa de Orçamentos Familiares - POF), considered for the empirical analysis. The first essay examines several dimensions of economic inequality, emphasizing the role of non-monetary income in compressing it. The results suggest that non-monetary income works as an insurance mechanism for low-income households. Nevertheless, Brazilian households seem to have difficulties in smoothing consumption. The second essay discusses further the measure of consumption at the microeconomic level and addresses the consumption patterns upon retirement. The results indicate no decline in \"core\" non-durable consumption (i.e., net of work-related). Moreover, accounting for the heterogeneity across households according to pension schemes, the core non-durable consumption increases upon retirement. The third essay addresses the effect of income inequality on conspicuous consumption by emphasizing how credit constraint operates in such a relationship. The results support the hypothesis of competitive status-seeking behavior and stand in line with evidence that relative comparisons deepen households\' indebtedness. The fourth essay studies the relationship between saving rate and permanent income. The study highlights that such a relationship depends on whether household saving comprises the investment in human capital. Assuming the latter as part of household savings, the saving rate increases in permanent income.